ESL TEACHERS’ BELIEFS ABOUT ASSESSMENT FOR LEARNING IN THE BOLE DISTRICT OF THE SAVANNA REGION OF GHANA - Owusu, Sefa (Institut Agama Islam Negeri (IAIN) Bone, 2024)
Assessment for learning or formative assessment is a process of gathering and analysing information about what learners know and can do and using that information to make instructional decisions. The role of assessment for learning, especially in an ESL classroom cannot be overemphasized. Among other things, formative assessments can go a long way in helping learners to set learning goals and prepare well for summative assessments. Regrettably, many teachers are unable to implement assessments for learning in their ESL classrooms. This study examined what the ESL teachers at Bole District of the Savanna Region of Ghana think about the assessment for learning, how they implement it, and the challenges they face in implementing it. The study adopted the mixed methods approach and the convergent parallel design. Census sampling was used to select all the 82 ESL teachers in the Bole District. The findings showed that ESL teachers had positive beliefs about assessment for learning practices. However, they did not implement it in their classrooms due to challenges such as inadequate time on timetables, large class sizes, lack of resources, limited access to technology, and overloaded English curriculum. It is recommended that school heads should make every endeavour to provide adequate time on timetables and they should also provide the ESL teachers with the needed assessment for learning resources for effective teaching and learning.